Pancreatic islet transplantation - Corrêa-Giannella Maria; Raposo do Amaral Alexandre S (Diabetology & Metabolic Syndrome, 2009)
Abstract Background No formulation of exogenous insulin available to date has yet been able to mimic the physiological nictemeral rhythms of this hormone, and despite all engineering advancements, the theoretical proposal of developing a mechanical replacement for pancreatic β cell still has not been reached. Thus, the replacement of β cells through pancreas and pancreatic islet transplantation are the only concrete alternatives for re-establishing the endogenous insulin secretion in type 1 diabetic patients. Since only 1 to 1.5% of the pancreatic mass corresponds to endocrine tissue, pancreatic islets transplantation arises as a natural alternative. Data from the International Islet Transplant Registry (ITR) from 1983 to December 2000 document a total of 493 transplants performed around the world, with progressively worse rates of post-transplant insulin independence. In 2000, the "Edmonton Protocol" introduced several modifications to the transplantation procedure, such as the use of a steroid-free immunosuppression regimen and transplantation of a mean islet mass of 11,000 islet equivalents per kilogram, which significantly improved 1-year outcomes. Although the results of a 5-year follow-up in 65 patients demonstrated improvement in glycemic instability in a significant portion of them, only 7.5% of the patients have reached insulin independence, indicating the need of further advances in the preservation of the function of transplanted islet. In addition to the scarcity of organs available for transplantation, islets transplantation still faces major challenges, specially those related to cell loss during the process of islet isolation and the losses related to the graft site, apoptosis, allorejection, autoimmunity, and immunosuppression. The main strategies to optimize islet transplantation aim at improving all these aspects. Conclusion Human islet transplantation should be regarded as an intervention that can decrease the frequency of severe hypoglycemic episodes and improve glycemic control in selected patient for whom benefits of 4-5 years duration would be very valuable. Its limitations, however, indicate that the procedure in its current format is not suitable for all patients with type 1 diabetes.